2011
DOI: 10.1371/journal.pone.0021740
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Protein Structural Maps of Adaptive Evolution of Human Influenza A Virus to Increased Virulence in the Mouse

Abstract: Adaptive evolution is characterized by positive and parallel, or repeated selection of mutations. Mouse adaptation of influenza A virus (IAV) produces virulent mutants that demonstrate positive and parallel evolution of mutations in the hemagglutinin (HA) receptor and non-structural protein 1 (NS1) interferon antagonist genes. We now present a genomic analysis of all 11 genes of 39 mouse adapted IAV variants from 10 replicate adaptation experiments. Mutations were mapped on the primary and structural maps of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
100
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(102 citation statements)
references
References 121 publications
2
100
0
Order By: Relevance
“…Human influenza A virus acquired the PB2 amino acid mutation E249G upon mouse adaptation (25), suggesting that the amino acid at position 249 probably is involved in some mechanism for adaptation to mammals. Sequence analysis showed that the prevalence of PB2 amino acid 249G in human seasonal H3N2 viruses was almost 50%.…”
Section: Discussionmentioning
confidence: 99%
“…Human influenza A virus acquired the PB2 amino acid mutation E249G upon mouse adaptation (25), suggesting that the amino acid at position 249 probably is involved in some mechanism for adaptation to mammals. Sequence analysis showed that the prevalence of PB2 amino acid 249G in human seasonal H3N2 viruses was almost 50%.…”
Section: Discussionmentioning
confidence: 99%
“…The PB2-588 position is located within the 627 domain and has been identified as a host-range-specific amino acid position (20,21); it is characteristic of human influenza viruses, contributes to virus replication in mammalian cells, and partially compensates for the lack of 627K (20,21). The PA-P224S mutation is located in the nuclear localization signal domain and may influence the transport and accumulation of PA in the nuclei of virus-infected cells (22). The PA-A70V mutation was identified in a mouse-adapted H1N1/09 virus and on its own in CA04 background did not cause lethality or a more than 10% weight loss (23), but we showed here that PA-A70V combined with PA-P224S significantly boosted the lethality and lung pathology of PA-P224S alone.…”
mentioning
confidence: 99%
“…induction, weight loss, pathology, and mortality in mice in an H3N2 background (29,30). We found D2N in 60% of sequencing reads in RCP5 and in 0% of reads in P1.…”
Section: Resultsmentioning
confidence: 68%